Trade policy in a sovereign Palestinian State: What are the options in a final settlement?. (22nd May 2022) - Agbahey, Johanes; Siddig, Khalid; Grethe, Harald; Luckmann, Jonas
Abstract: This paper quantifies the economy‐wide effects of different trade policies on the Palestinian economy, using a detailed database and a general equilibrium model adjusted to the particularities of the Palestinian economy. The findings show that a liberal and non‐discriminatory trade regime provides the highest benefits for the Palestinian economy, in terms of welfare effects, GDP growth and job creation. The choice of an exchange rate regime has a considerable influence on the effects of trade policy. Accordingly, a full control over trade and monetary policy instruments could improve the capacity of the Palestinian National Authority to address the prevailing high unemployment and sluggish economic growth.